What Interventional Cardiologists Are Still Leaving to the Surgeons? - Promphan, Worakan; Qureshi, Shakeel A. (Frontiers in Pediatrics, 2016)
Nowadays, development of new technologies is still ongoing with the ultimate goal of maximizing treatment outcomes with less invasiveness and reduced procedural risk. This review is intended to update on when interventionalists need surgical support in common or emerging problems in congenital heart disease.